Strategic Management of Early Childhood Caries in Thailand: A Critical Overview - Sitthisettapong, Thanya; Tasanarong, Parinda; Phantumvanit, Prathip (Frontiers in Public Health, 2021)
The aim of this report was to advocate early childhood caries (ECC) and share strategic management in Thailand, despite over two decades of free Universal Health Coverage including oral healthcare. The recent Thai national oral health survey in 2017 indicates the very high prevalence of ECC, with an average of three carious teeth affected in 53% of 3-year-old children. This is despite the efforts of the Ministry of Public Health that has launched several interventional programs ranging from an upstream policy that prohibits sugar additions in baby formula milk to downstream remediations such as advocating and encouraging toothbrushing with fluoride toothpastes. Nevertheless, ECC is strongly predicated by other key factors including the family and community commitment and participation, as embodied in the current World Health Organization guidelines. These encompass three different tiers of community-level prevention: primary, secondary, and tertiary. Accordingly, the following strategies for ECC management in Thailand should be based at primary care clusters (PCC) in sub-district health centers, with the assistance of inter-professional health teams. These include community education on the importance of deciduous teeth and effective toothbrushing with fluoride toothpaste (primary prevention), regular examination and detection of ECC lesions and early intervention (secondary prevention), insertion of non-invasive preventive restorations using cost-effective atraumatic restorative treatment (ART) or simplified and modified ART (SMART) (tertiary prevention), and, finally, effective follow-up and monitoring systems. It is anticipated that this triple tier approach to ECC management will improve not only the oral health but also the overall children's health.